Role of Gut Microbiome in COVID-19: An Insight Into Pathogenesis and Therapeutic Potential - Hussain, Ikram; Cher, Gabriel Liu Yuan; Abid, Muhammad Abbas; Abid, Muhammad Bilal (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), resulted in an unprecedented global crisis. Although primarily a respiratory illness, dysregulated immune responses may lead to multi-organ dysfunction. Prior data showed that the resident microbial communities of gastrointestinal and respiratory tracts act as modulators of local and systemic inflammatory activity (the gut-lung axis). Evolving evidence now signals an alteration in the gut microbiome, brought upon either by cytokines from the infected respiratory tract or from direct infection of the gut, or both. Dysbiosis leads to a ‘leaky gut'. The intestinal permeability then allows access to bacterial products and toxins into the circulatory system and further exacerbates the systemic inflammatory response. In this review, we discuss the available data related to the role of the gut microbiome in the development and progression of COVID-19. We provide mechanistic insights of early data with a focus on immunological crosstalk and the microbiome’s potential as a biomarker and therapeutic target.